Canopy conductance in a two‐storey Siberian boreal larch forest, Russia. Issue 6 (18th May 2014) - Xue, Bao‐Lin; Li, Zhanling; Yin, Xin‐An; Zhang, Tieliang; Iida, Shin'ichi; Otsuki, Kyoichi; Ohta, Takeshi; Guo, Qinghua
Abstract A larch forest in eastern Siberia was characterized by the presence of two distinct storeys, the overstorey with a small leaf area index (LAI) and a dense understorey with a relatively large LAI. To understand the roles of the overstorey and understorey in forest–atmosphere water exchange, canopy conductance (Gc), a critical parameter used in determining the energy and mass exchange, was calculated on the basis of latent heat flux above the overstorey and understorey, measured separately. Results showed that Gc for the overstorey (Gco) and understorey (Gcu) experienced different seasonal fluctuations. Gco was smaller than Gcu during periods of leaf expansion and leaf fall and showed an increasing trend until 1 month after the onset of leaf expansion. In contrast, a sharp decrease in Gco was observed immediately before onset of leaf fall. Furthermore, Gco was slightly larger than Gcu during the fully foliated period. A simple model using solar radiation and vapour pressure deficit (D) as inputs successfully reproduced the Gc in fully foliated periods with acceptable accuracy. Furthermore, both the understorey and overstorey in this study have a large reference Gc (Gc at D = 1 KPa) than their counterparts of other boreal forests and would not be able to sustain a constant leaf–soil water potential difference as D increases. We speculated that this confers the forest with an advantage allowing it to be able to sustain carbon assimilation during large D days and thus provides for the survival of the ecosystem during the short growing season at this site. Copyright © 2014 John Wiley & Sons, Ltd.